The Association Between Environmental and Social Factors and Myopia: A Review of Evidence From COVID-19 Pandemic - Jirawut Limwattanayingyong; Anyarak Amornpetchsathaporn; Methaphon Chainakul; Andrzej Grzybowski; Andrzej Grzybowski; Paisan Ruamviboonsuk (Frontiers Media S.A., 2022)
PurposeTo review the association between children's behavioral changes during the restriction due to the pandemic of Coronavirus disease (COVID-19) and the development and progression of myopia.DesignA literature review.MethodWe looked for relevant studies related to 1) children's behavioral changes from COVID-19 restriction and 2) children's myopia progression during COVID-19 restriction by using the following keywords. They were "Behavior," "Activity," "COVID-19," "Lockdown," "Restriction," and "Children" for the former; "Myopia," "COVID-19," "Lockdown," "Restriction" for the latter. Titles, abstracts and full texts from the retrieved studies were screened and all relevant data were summarized, analyzed, and discussed.ResultsChildren were less active and more sedentary during COVID-19 restriction. According to five studies from China and six studies, each from Hong Kong, Spain, Israel, South Korea, Turkey and Taiwan included in our review, all countries without myopia preventive intervention supported the association between the lockdown and myopia progression by means of negative SER change ranging from 0.05-0.6 D, more negative SER change (compared post- to pre-lockdown) ranging from 0.71-0.98 D and more negative rate of SER changes (compared post- to pre-lockdown) ranging from 0.05-0.1 D/month. The reported factor that accelerated myopia is an increase in total near work, while increased outdoor activity is a protective factor against myopia progression.ConclusionThe pandemic of COVID-19 provided an unwanted opportunity to assess the effect of the behavioral changes and myopia in the real world. There is sufficient evidence to support the association between an increase in near work from home confinement or a reduction of outdoor activities and worsening of myopia during the COVID-19 lockdown. The findings from this review of data from the real world may help better understanding of myopia development and progression, which may lead to adjustment of behaviors to prevent myopia and its progression in the future.